THE WEST DOMINATION TOWARDS THE EAST IN LIFEBUOY CLINI-SHIELD 10 ADVERTISEMENT: ORIENTALISM STUDY - Kamalia, Mirza Fathima Jauhar (JURNAL ILMU BUDAYA, 2015)
Lifebuoy Clini-Shield 10 soap claims that its product kills the bacteria and protects the skin ten times better than any other famous anti bacterial soaps. The advertisement chooses to use the West researcher as the model who finds the new technology called as Activ Naturol Shield inorder to attract and convince the buyers and use the East people as the object of the research. Furthermore, Lifebuoy Clini-Shield 10 is shown as the result of product by the West researcher and as the solution for the health problem. This study aims to explain the image of the Westdomination depicted in Lifebuoy Clini-Shield 10. This study will use the theory of Orientalism by Edward Said to answer the problem above. This study uses qualitative method supported with the data of the advertisement video, as the main source of the data, and some information from the website of the Lifebuoy Indonesia. The results of the study show that the West is depicted as the leader, the source of the knowledge and the inventor of the technology through the Westresearcher. As the effect, people will internalize the hegemony that the West is the most superior nation among the other nations whose people born to lead the world and the East will consider themselves as the inferior nation and must depend on to the West to solve every problem thatthey have.Keywords: Domination, Orientalism, Superior, Advertisement.